Oxidized LDL activated eosinophil polarize macrophage phenotype from M2 to M1 through activation of CD36 scavenger receptor. (August 2017) - Qin, Minghui; Wang, Lai; Li, Fuqiang; Yang, Mingjie; Song, Lei; Tian, Fang; Yukht, Ada; Shah, Prediman K.; Rothenberg, Marc E.; Sharifi, Behrooz G.
Abstract: Background and aims: Inflammation, particularly innate immunity, plays an important role in cardiovascular diseases. The aim of this study was to investigate whether atherogenic determinants such as oxidized LDL modulate the phenotype of eosinophils. Methods: Cultured eosinophils were treated with oxidized LDL and the expression of selective inflammatory and anti-inflammatory cytokines was determined. In addition, the eosinophil receptor and signaling that mediate these events were identified. Results: Treatment of cultured eosinophils with oxidized LDL (Ox-LDL) specifically induced the expression of IFNα and IFNβ without affecting expression of other proinflammatory cytokines, such as TNFα, IL-1β, and IL-6. In macrophages, Ox-LDL downregulated expression of both IFNα and IFNβ, suggesting that the effect of Ox-LDL on the expression of type I interferons is specific to eosinophils. Furthermore, we noted that eosinophils constitutively expressed IL-4 and IL-13, and Ox-LDL markedly downregulated their expression. Analysis of Ox-LDL signaling revealed that eosinophils constitutively expressed SRB2, CD36, and CD68 scavenger receptors, and Ox-LDL markedly induced the expression of CD36. Further analysis of CD36 signaling by siRNA and neutralizing antibodies showed that the induction of type I IFN by Ox-LDL is mediated by CD36 signaling whereas downregulation of IL-4 is independent of CD36 activation. We further showed that peritoneal macrophages treated with condition medium collected from Ox-LDL treated eosinophils markedly induced the expression of M1 markers such as iNOS, IL6, SOSC3 and TNFα whereas the condition medium from non-treated eosinophils significantly induced expression of M2 markers like ARG1 and CCL24. Conclusions: Our data suggest that an atherogenic condition could activate eosinophils and modulate the phenotype of macrophages (from M2 to M1 phenotype), in part, through the CD36 receptor signaling. Highlights: Inflammation is associated with atherosclerosis. Eosinophils are activated by hyperlipidemia. CD36 scavenger receptor mediates uptake of ox-LDL by eosinophils.